2021
DOI: 10.3390/stresses1030014
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Role of Nitric Oxide, Ethylene, Nitrogen, and Sulfur in Plant Salt Stress Tolerance

Abstract: Salt stress significantly contributes to major losses in agricultural productivity worldwide. The sustainable approach for salinity-accrued toxicity has been explored. The use of plant growth regulators/phytohormones, mineral nutrients and other signaling molecules is one of the major approaches for reversing salt-induced toxicity in plants. Application of the signaling molecules such as nitric oxide (NO) and ethylene (ETH) and major mineral nutrient such as nitrogen (N) and sulfur (S) play significant roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 160 publications
(217 reference statements)
0
5
0
Order By: Relevance
“…Sulfur metabolism plays a vital role in the process of biological stress resistance. Sulfur has been reported to have essential functions in plants’ salt adaptation, active oxygen elimination, and heat adaptation ( Ali et al, 2021 ; Jahan et al, 2021 ; Zhou et al, 2022 ), while cyanobacteria have a similar sulfur metabolism as plants ( Kharwar et al, 2021 ). Consistantly, sulfur metabolism-related genes were significantly up-regulated in WT and Syn7942/Δsps-ect compared to reference conditions ( Figures 5A , C ).…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur metabolism plays a vital role in the process of biological stress resistance. Sulfur has been reported to have essential functions in plants’ salt adaptation, active oxygen elimination, and heat adaptation ( Ali et al, 2021 ; Jahan et al, 2021 ; Zhou et al, 2022 ), while cyanobacteria have a similar sulfur metabolism as plants ( Kharwar et al, 2021 ). Consistantly, sulfur metabolism-related genes were significantly up-regulated in WT and Syn7942/Δsps-ect compared to reference conditions ( Figures 5A , C ).…”
Section: Resultsmentioning
confidence: 99%
“…Salinity disrupts ion homeostasis, leading to increased Na + and Cl − ion concentrations and inhibiting the uptake of K + ions in the cytosol of plant cells, thereby affecting cellular metabolism and decreasing the plants' tolerance to stress (Wu et al, 2018). Salt stress causes a rapid depolarization of the plasma membrane potential causing activation of voltage‐gated guard cell outward rectifying K + (GORK) channels, resulting in the efflux of K + ions (Jahan, Rasheed, et al, 2021). The present study showed that melatonin decreased Na + ions and increased K + ions in leaves under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, soil salinization has become a major global challenge with its deleterious impacts on agricultural productivity (Peng et al, 2019). Plants grown on saline soil suffer from ion toxicity and exhibit increased production of reactive oxygen species (ROS), and an impaired soil nitrogen (N) cycle (Jahan, Rasheed, et al, 2021;Khan & Hemalatha, 2016;Liu et al, 2018). Salt stress has a significant impact on photosynthesis (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…NO is considered a phytohormone for some authors [ 37 ] while other ones do not consider it as such since no specific receptors for NO have been identified [ 21 ]. The action of NO is mainly mediated with its roles through post-translational modifications, including tyrosine nitration, metal nitrosylation and S -nitrosylation [ 19 , 25 ].…”
Section: No and Gsno In Plantsmentioning
confidence: 99%
“…In relation to mineral stresses, NO and/or GSNO have been implicated in several of them, including responses to heavy metals (e.g., Cu, Fe, Cd or Al; Refs. [ 27 , 32 , 59 , 60 , 61 ]), to metalloids [ 62 ], to salinity [ 37 , 63 , 64 ] or to nutrient deficiencies (see below). In general, NO production increases in roots under several mineral stresses.…”
Section: Role Of No and Gsno In The Responses Of Plants To Mineral St...mentioning
confidence: 99%